Petrogenesis of the Chaihulanzi Gneiss and its Tectonic Implications for the North China Craton. (29th December 2021) - QU, Yunwei; XIE, Yuling; XIA, Jiaming; YU, Chao; XU, Dong; LI, Xu; SUN, Li
Abstract : Abstract: The Chaihulanzi area in eastern Inner Mongolia is tectonically situated on the northern margin of the North China Craton (NCC). The main Precambrian lithologies of the area have been referred to the Archean Jianping Group meta‐supracrustal sequences. Based on field observations, petrographic, whole‐rock geochemical, and zircon U‐Pb geochronological results, a magmatic origin for the units is proposed. Our results show that the Chaihulanzi gneisses are mainly of granitic, dioritic and granodioritic compositions, and show typical magmatic rock textures and mineral assemblages. The dioritic and granodioritic gneisses show Na‐rich tonalite–trondhjemite–granodiorite (TTG)‐like affinity with zircon U‐Pb dates of ca. 2.57–2.59 Ga, representing a juvenile continental growth for the northeastern NCC. The granitic gneiss is indeed potassic granite and yielded a zircon U‐Pb date of ∼2.50 Ga, which is contemporaneous with the Jining–Jiaoliao microblock collision (2.53–2.49 Ga), implying another crustal growth event. The well‐developed gneissosity in 2.57–2.59 Ga dioritic and granodioritic gneisses together with the 2.5 Ga potassic granite, which crosscuts the gneissosity implies a 2.57–2.50 Ga (mainly 2.53–2.51 Ga) collisional orogeny, probably related to the Jining–Jiaoliao microblock collision. Our new geology and chronological results provide new evidence for the early Precambrian tectonic evolution of the NCC.